2005
DOI: 10.1111/j.1479-828x.2005.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low immunity to rubella infection on antenatal screening

Abstract: Programs targeting underimmunised populations for rubella vaccination should focus on overseas-born women, particularly those born in Asia, nulliparous women and also women > 35 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
6
18
0
1
Order By: Relevance
“…However, it is difficult to compare prevalences obtained in different seroprevalence studies due to differences in sampling methods, populations studied and serological tests used. The prevalence of protective antirubella IgG titres found in this study in pregnant women (95 %) was similar to the prevalence found in pregnant women in the United States of America (98 %) [37], Colombia (93 %) [33], Brazil (92 %) [34], Iran (96 %) [30], Turkey (94-100 %) [36,39] and Australia (93 %) [31], while it was higher than the prevalence found in Taiwan (89 %) [40], Germany (87 %) [41], Sudan (72 %) [42] and Poland (89 %) [35]. The prevalence of protective anti-measles titres found in this study in pregnant women (89 %) was similar to the prevalence found in pregnant women or neonates in the United States of America (88 %) [37], Argentina (87 %) [28], Japan (80-90 %) [29] and China (90 %) [43], while it was higher than the prevalence found in Germany (79 %) [41] and Iran (82 %) [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it is difficult to compare prevalences obtained in different seroprevalence studies due to differences in sampling methods, populations studied and serological tests used. The prevalence of protective antirubella IgG titres found in this study in pregnant women (95 %) was similar to the prevalence found in pregnant women in the United States of America (98 %) [37], Colombia (93 %) [33], Brazil (92 %) [34], Iran (96 %) [30], Turkey (94-100 %) [36,39] and Australia (93 %) [31], while it was higher than the prevalence found in Taiwan (89 %) [40], Germany (87 %) [41], Sudan (72 %) [42] and Poland (89 %) [35]. The prevalence of protective anti-measles titres found in this study in pregnant women (89 %) was similar to the prevalence found in pregnant women or neonates in the United States of America (88 %) [37], Argentina (87 %) [28], Japan (80-90 %) [29] and China (90 %) [43], while it was higher than the prevalence found in Germany (79 %) [41] and Iran (82 %) [30].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the study showed a null correlation between anti-rubella IgG titres and maternal age. Seroprevalence studies carried out in other countries found positive correlations between the anti-measles IgG titres in neonates/pregnant women and maternal age [14,[28][29][30], and positive [28], negative [31][32][33][34][35] or null [36,37] correlations between the anti-rubella IgG titres in neonates/ pregnant women and maternal age. The present study found the prevalence of protective antirubella IgG titres to be similar in the neonates of autochthonous and immigrant women (96.9 vs. 95.2 %).…”
Section: Discussionmentioning
confidence: 99%
“…17 Measurements of rubella antibodies during antenatal visits at the Royal London Hospital in 2000 showed that 9% of Asian immigrants were seronegative compared with 2% of whites. 18 Another study found that 10.0% of pregnant Asian immigrants in Catalonia, Spain, were susceptible to rubella, compared with 5.4% of pregnant women born indigenously.…”
Section: Discussionmentioning
confidence: 99%
“…De ser cierto lo anterior, las características étnicas de estas comunidades pueden tener alguna relevancia en la protección contra la infección por el virus de la rubéola. Los estudios muestran diferencias significativas entre grupos étnicamente diferentes (38,39). La realización de este estudio antes de la vacunación, aclararía estas dudas.…”
Section: Discussionunclassified